2020
DOI: 10.21608/ejnh.2020.166695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quinoa (Chenopodium quinoa) on Lipid Profile in Rats Exposed to twoSynthetic Food colors

Abstract: Increasing scientific evidence suggests potential adverse effects on children's health from synthetic chemicals used as food additives. Synthetic food colors are food additives are widely used as colorants in food. This study was conducted to investigate the effectiveness of quinoa powder as nutraceuticals on lipids profile for young experimental rats exposed to chronic administration of synthetic food colores (azo dyes),chocolate brown (CH) or sunset yellow (SY). Seventy healthy young male albino rats "Spragu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Altered lipid profile in blood serum observed in rats fed with common azo dye during this study also agree with other studies (Saxena and Sharma, 2015;El-Desoky et al, 2017;Reza et al,2019). Sharma et al (2009) and Bahnasy and Ragheb (2020) reported changes in lipid profile of rats fed with other food colours also viz., sunset yellow and chocolate brown. Significantly greater concentration of TC and TG has also been reported in rats when administered to fast green orally (Turley 2004;Ashour and Abdelaz, 2009).…”
Section: Environment Conservation Journalsupporting
confidence: 92%
See 1 more Smart Citation
“…Altered lipid profile in blood serum observed in rats fed with common azo dye during this study also agree with other studies (Saxena and Sharma, 2015;El-Desoky et al, 2017;Reza et al,2019). Sharma et al (2009) and Bahnasy and Ragheb (2020) reported changes in lipid profile of rats fed with other food colours also viz., sunset yellow and chocolate brown. Significantly greater concentration of TC and TG has also been reported in rats when administered to fast green orally (Turley 2004;Ashour and Abdelaz, 2009).…”
Section: Environment Conservation Journalsupporting
confidence: 92%
“…Other researchers also studied that plant extracts could be effective means for reducing toxicity caused by food colours. Bahnasy and Ragheb (2020) studied ameliorative effect of Chenopodium quinoa for toxicity caused by chocolate brown and sunset yellow and observed significant decrease in TC, TG and LDL and significant increase in HDL treated with its extract along with food colour. Yanam et al, (2020) also reported that quinoa could ameliorate the hyperlipidaemic condition induced by high fat diet.…”
Section: Environment Conservation Journalmentioning
confidence: 99%